2020
DOI: 10.1080/19491247.2020.1803533
|View full text |Cite
|
Sign up to set email alerts
|

A home for xenophobia: U.S. public housing policy under Trump

Abstract: Elected after espousing xenophobic rhetoric and policy proposals, President Donald Trump has pursued an anti-immigrant approach to governance that spans multiple areas of policy and practice in the U.S., including public housing. In this essay, we argue that the Trump Administration has pursued a variety of egregious examples of xenophobic policies, but far from anomalies, these actions are in keeping with the long historical tradition of xenophobia in the U.S. In the area of public housing, policy changes tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The events of the last several years have only heightened the politicization of K-12 schooling (Finkel et al, 2020). The Trump presidency (2016–2020) was marked by a resurgence of xenophobic discourse that targeted and scapegoated immigrant communities, a proliferation of white nationalist groups, and concerted efforts to restrict voting rights in ways that disfranchise communities of color (Allen & Goetz, 2021; Thrush & Haberman, 2017). Further, 2020 was a year marked by ongoing protests against systemic violence by police.…”
Section: Education Within a Shifting Sociopolitical Contextmentioning
confidence: 99%
“…The events of the last several years have only heightened the politicization of K-12 schooling (Finkel et al, 2020). The Trump presidency (2016–2020) was marked by a resurgence of xenophobic discourse that targeted and scapegoated immigrant communities, a proliferation of white nationalist groups, and concerted efforts to restrict voting rights in ways that disfranchise communities of color (Allen & Goetz, 2021; Thrush & Haberman, 2017). Further, 2020 was a year marked by ongoing protests against systemic violence by police.…”
Section: Education Within a Shifting Sociopolitical Contextmentioning
confidence: 99%
“…Thus, these studies suggest that constant contact between immigrants and the public can help improve knowledge sharing and cultural assimilation, and reduce conflicts (Ceobanu & Escandell, 2008 ; Stangor et al, 1996 ). Although the existing literature have found that contact between immigrants and the public reduces negative perceptions about immigrants caused by issues of racism, false knowledge, xenophobia, and others (Allen & Goetz, 2021 ; Kilty & Haymes, 2000 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A core foundation of the Trump presidential campaign was building a wall at the U.S.-Mexico border as one of multiple strategies to prevent immigrant entry (Verney, 2018). Once elected, proposed and enacted exclusionary immigration policies continued, including entry bans from select nations (Allen & Goetz, 2021; Kanno-Youngs, 2021), ending of the Deferred Action for Childhood Arrivals (DACA; Romo et al, 2017), reduced access to asylum (Center for Migration Studies, 2021), and increased use of border detentions (Garrett, 2020; Verea, 2018).…”
Section: Introductionmentioning
confidence: 99%